2010
DOI: 10.1007/s11947-010-0470-x
|View full text |Cite
|
Sign up to set email alerts
|

Acrylamide in Foods: Chemistry and Analysis. A Review

Abstract: Acrylamide is a potential cause of a wide spectrum of toxic effects and is classified as probably "carcinogenic in humans". The discovery of acrylamide in human foods has given rise to extensive studies exploring its formation mechanisms and levels of exposure and has spurred search into suitable analytical procedures for its determination in foodstuffs. However, the exact chemical mechanisms governing acrylamide formation are not yet known and cheap, convenient, and rapid screening methods are still to be dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(45 citation statements)
references
References 100 publications
0
44
0
1
Order By: Relevance
“…For each of the 10 product categories, the Recommendation gives detailed provisions concerning subcategories to be sampled and in case of French fries from potato dough also the time point (March/November) for sampling. A number of comprehensive reviews on analytical methods for the determination of AA in food products were published during the past decade (Wenzl et al, 2003;Stadler and Scholz, 2004;Zhang et al, 2005;Keramat et al, 2011;Oracz et al, 2011;Tekkeli et al, 2012;Arvanitoyannis and Dionisopoulou, 2014;Elbashir et al, 2014). The following paragraphs give a short summary on the general procedures and main conclusions, but do not claim for completeness.…”
Section: Sample Collection and Frequencymentioning
confidence: 99%
“…For each of the 10 product categories, the Recommendation gives detailed provisions concerning subcategories to be sampled and in case of French fries from potato dough also the time point (March/November) for sampling. A number of comprehensive reviews on analytical methods for the determination of AA in food products were published during the past decade (Wenzl et al, 2003;Stadler and Scholz, 2004;Zhang et al, 2005;Keramat et al, 2011;Oracz et al, 2011;Tekkeli et al, 2012;Arvanitoyannis and Dionisopoulou, 2014;Elbashir et al, 2014). The following paragraphs give a short summary on the general procedures and main conclusions, but do not claim for completeness.…”
Section: Sample Collection and Frequencymentioning
confidence: 99%
“…Another important issue is the analysis of antibiotics in foods [85], including different legal aspects related to their determination and subsequent validation of the analytical methodologies [86]. Robust analytical methods are continuously under development in order to improve the figures of merit (analysis speed, resolution, and sensitivity), allowing the fast and sensitive analysis of other food contaminants as well as possible dangerous compounds generated during food processing as acrylamide [87,88], melatonin [89], N-nitrosamines [90], dioxins and dioxin-like PCBs [91], polycyclic aromatic hydrocarbons [92], Sudan dyes [93], food taints and offflavours [94], thiols in wine [95], and sulphites in food and beverages [96].…”
Section: Food Analysis: Current State Of the Art Methodologies And mentioning
confidence: 99%
“…Carbonyl compounds produced in the lipid oxidation pathway competes with carbohydrate-derived carbonyls for amino compounds to produce carbonyl-amine reaction products (Zamora, 2011) Researchers have found that acrylamide possesses neurotoxicity, genetic toxicity and carcinogenicity (Friedman, 2003;Hagmar, Wirfält, Paulsson, & Törnqvist, 2005;Jafari, 2011;Keramat, 2011). Acrylamide is mainly produced by the reaction between some amino acids and reducing sugar on high temperature or during the pathway of maillard reaction (Stadler et al, 2002 ;Jafari, 2011;Keramat, 2011). Amino acid combined with a dicarbonyl compound and then subjected to intramolecular rearrangement of ion and strecker degradation to form an acrolein, a hydrogen nitride and other compounds or strecker aldehyde (Donald, et al, 2002).…”
Section: Acrylamide Formationmentioning
confidence: 99%